Analysis of the Implementation of Article 22 Paragraph (2) of ATR/BPN Ministerial Regulation Number 6 of 2018 on Complete Systematic Land Registration (PTSL): Limitations and Challenges in Recording Proof of Community Land Ownership - Taufiq, Fida Nabilah; Masykur, M. Hamidi; Supriyadi (The Islamic Education and Multiculturalism Foundation, 2024)
The problem of incomplete or non-existent land ownership proof among the community has arisen in one of the villages in Sidoarjo Regency. This is rooted in the registration of land through the Comprehensive Systematic Land Registration (PTSL) program by one of the heirs named